The legitimacy of Scandinavian libraries, archives and museums as public spheres: Views from the professionals. (June 2023) - Larsen, Håkon; Kann-Rasmussen, Nanna; Rydbeck, Kerstin
This article analyses how library, archive and museum professionals legitimize the use of scarce societal resources for maintaining their respective organizations, with a special emphasis on their role as public-sphere infrastructure. Drawing on data from a survey among professionals in libraries, archives and museums in Denmark, Norway and Sweden, the authors investigate whether professionals across these institutions have similar expectations of their organizations to serve as public spheres. The analysis is contextualized with references to current library, archive and museum legislation across the three countries. The authors conclude that there are many similarities across the three countries, although national library, archive and museum legislation differs. This is interpreted in light of new public governance being a dominant regime of governance.